PENGARUH EMPLOYEE RELATION TERHADAP KINERJA KARYAWAN PADA JIMMY BUTCHER URBAN STORE - Ni Wayan Dian Irmayani; I Nyoman Wahyu Widiana; Luh Putu Angelita Wulandari (Universitas Mahendradatta, 2022)
Performance as a result of work in quality and quantity that can beachieved by an employee in carrying out tasks in accordance with theresponsibilities assigned to him. One of the factors that affect employeeperformance is employee relations. The population of this research is JimmyButcher Urban Store employees, which are 30 employees. Because thepopulation is less than 30 people, detecting samples using saturated samples isby using the entire population as the research sample. Data collection is donethrough a questionnaire. The results showed that employee relations had apositive effect on employee performance. so it can be said that an increase inemployee relations will be followed by an increase in employee performance